Analisis hubungan lama penggunaan gadget dengan perkembangan emosional pada anak usia prasekolah - Rodhyatun Ulfa; Herry Susanto; Indra Tri Astuti (JOURNAL OF Community Health Issues, 2026)
Background: Preschool-aged children are increasingly exposed to gadgets, which can significantly impact their emotional development. Excessive gadget use without parental supervision is known to impair emotional regulation, while controlled usage with appropriate guidance can support healthy emotional development. Purpose: To analyze the relationship between the duration of gadget use and emotional development among preschool-aged children. Method: This study employed a quantitative research design with a correlational method using a cross-sectional approach. A total of 100 preschool-aged children participated as respondents, selected through purposive sampling method. Data analysis was conducted using Spearman Rank correlation test at a significance level of α = 0.05. Results: The majority of respondents demonstrated prolonged gadget usage (>2 hours/day), with significant variations in emotional development. The Spearman Rank test revealed a significant correlation between duration of gadget use and emotional development (p < 0.05), indicating a negative relationship where longer gadget exposure was associated with poorer emotional regulation and increased behavioral problems. Conclusion: Data analysis demonstrated a meaningful correlation between gadget usage duration and emotional development among preschool-aged children. The longer the duration of gadget use, particularly without parental supervision, the greater the tendency for emotional developmental issues.   Keywords: Emotional Development; Gadget Usage; Preschool Children.   Pendahuluan: Anak usia prasekolah semakin terpapar penggunaan gadget yang dapat berdampak signifikan terhadap perkembangan emosional mereka. Penggunaan gadget yang berlebihan tanpa pengawasan orang tua diketahui dapat mengganggu regulasi emosi, sementara penggunaan terkontrol dengan bimbingan yang tepat dapat mendukung perkembangan emosional yang sehat. Tujuan: Untuk menganalisis hubungan lama penggunaan gadget dengan perkembangan emosional pada anak usia prasekolah. Metode: Studi ini menerapkan rancangan penelitian kuantitatif dengan metode korelasional melalui pendekatan potong lintang (cross-sectional). Jumlah responden yang terlibat sebanyak 100 anak usia prasekolah yang ditentukan menggunakan metode purposive sampling. Pengolahan data dilaksanakan dengan uji korelasi Spearman Rank pada taraf signifikansi α sebesar 0,05. Hasil: Sebagian besar responden menunjukkan penggunaan gadget yang berkepanjangan (>2 jam/hari) dengan variasi signifikan dalam perkembangan emosional. Uji Spearman Rank menunjukkan ditemukan keterkaitan yang signifikan antara lama penggunaan gadget dan perkembangan emosional (p < 0,05), menunjukkan hubungan negatif dimana paparan gadget yang lebih lama berkaitan dengan regulasi emosi yang lebih buruk dan peningkatan masalah perilaku. Simpulan: Analisis data menunjukkan keterhubungan yang bermakna antara lama penggunaan gadget dengan perkembangan emosional pada anak usia prasekolah. Semakin lama durasi penggunaan gadget, khususnya tanpa pengawasan orang tua, semakin besar kecenderungan munculnya masalah perkembangan emosional.   Kata Kunci: Anak Prasekolah; Penggunaan Gadget; Perkembangan Emosional.